Language in Interrogation: Building Understanding and Humanistic Justice through Forensic Analysis - Saud, Jefriyanto; Murtadho, Fathiaty; Rasyid, Yumna (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Language plays a central role in legal interrogation, particularly in the construction of official Examination Reports (Berita Acara Pemeriksaan/BAP). This study aims to analyze forms of interrogative questions in BAP related to defamation or hate speech cases that potentially generate psychological pressure or bias toward the examinee. It also formulates recommendations for more communicative and fair interrogative language as part of humanistic justice. The data are textual utterances extracted from BAP documents, analyzed through a forensic linguistic and psychopragmatic approach. To explore how meaning is coordinated and negotiated in interrogative exchanges, this study applies Herbert H. Clark’s (1996) theory of Joint Action and Common Ground, which views language use as a socially coordinated activity. This framework allows an examination of whether interrogative structures facilitate mutual understanding or reinforce asymmetrical power relations. Linguistic tendency analysis is used to measure the dominance of question types. Findings suggest that closed and suggestive questions prevail, limiting dialogic interaction. This study contributes to the field of Indonesian Language and Literature Education by promoting critical awareness of institutional language and advocating peace-oriented, humanistic language practices. Keywords: forensic linguistics; psychopragmatics; interrogation discourse; humanistic justice